The Mongrel Mob or Head Hunters? The association between neighbourhood-level factors on different types of gang membership in Aotearoa/New Zealand - Breetzke, Gregory D (Journal of criminology, 2022)
Previous research has shown that gang members typically emerge from more socially disorganised neighbourhoods. What is less known however is whether members of different types of gangs emerge from the same types of neighbourhoods. In this study, we use the social disorganisation theory as a framework to examine the spatial risk factors associated with two different types of gangs in New Zealand: Outlaw Motorcycle Gangs and New Zealand Adult Gangs. Overall, we found some consistency in spatial risk factors associated with gang membership by type in New Zealand; however, certain variables were significantly predictive of one type of gang membership but not of the other. The overall performance of our models also differed marginally depending on the type of gang being examined. In fact, our findings suggest some non-uniformity in the extent to which the various social disorganisation factors impact gang membership rates by type. The implications of this finding are discussed in the context of an ever-changing gang landscape in the country.